Pelatihan Pemantauan Status Gizi Anak Sekolah Pada Guru MI/SD Islam Di Ungaran Barat - Indri Mulyasari; Sugeng Maryanto; Puji Afiatna (Jurnal Pengabdian Ilmu Kesehatan, 2023)
MI/Elementary School has obligation to monitor nutritional status of their students. This is intended for early screening of nutritional problems to prevent negative impacts that might occur. Implementation of nutritional status monitoring at schools were still found several problems. The teacher has not been able to measure correctly and cannot assess the nutritional status of school aged children. This community service program was consist of lecture activities and short course of nutritional status monitoring of school aged children. The course was conducted in MI Nyatnyono 02 West Ungaran. The participants came from nine school representatives from ten invited schools in West Ungaran. The program aimed to improve teacher’s skills of nutritional status monitoring of their students. During the program, participants showed high enthusiasm. The result of the program is teacher’s skills in measuring weight and height has improve.